Ambition redefined : why the corner office doesn't work for every woman & what to do instead - Sollmann, Kathryn (Tantor Media, 2019)
Ambition Redefined is a timely alternative to current women's business books that define professional ambition and success as climbing the corporate ladder. In fact, this is not a path that all women want or should feel pressured to follow. Sollmann's focus is on the more critical and widespread workplace issue for everyday women-to always work in a way that fits their lives alongside their two major caregiving roles: for children and aging parents. Sollmann debunks common assumptions such as: IT'S NOT "WORTH IT" UNLESS THE SALARY IS HIGH. Women forfeit up to 4X their salaries every year out of the workforce to care for children and/or elderly parents-and it does not take a six-figure salary to achieve long-term financial security. FINDING FLEXIBLE WORK IS IMPOSSIBLE. Sollmann shines a bright light on the ever-widening world of flexwork-where women can find many interesting and exciting ways to tuck all generations of their families into a future that is financially secure and safe. WORK ENDS AT AGE SIXTY-FIVE. Women who leave the workforce and want to return in their forties, fifties, or sixties will be in good company as the ranks of older workers rise.